Navigating the care between two distinct cultures: a qualitative study of the experiences of Arabic-speaking immigrants in Norwegian hospitals - Tariq Alkhaled; Gudrun Rohde; Birgit Lie; Berit Johannessen (BMC, 2022)
Abstract Background During the past decades, there has been an increase in the number of immigrants to European and Scandinavian countries. This has challenged the health-care systems, which cater to the needs of patients despite their cultural and linguistic barriers, in these countries. Most studies on this topic have focused on the perspectives of health-care providers in delivering their service. The purpose of this qualitative study was to explore how hospitalized Arabic-speaking patients experienced their interaction with the Norwegian health-care system. Methods In-depth interviews with 20 participants and researcher's participant observation were conducted to explore the idiosyncratic details and ascribed meanings that foreign-born patients attach to their everyday experience of the Norwegian health-care system. Thematic analysis was performed on the transcribed and translated versions of the in-depth interviews. Results The findings of this study indicated three interrelated core themes. Firstly, there exist challenges in understanding and being understood because of linguistic and cultural differences of newly migrated patients. Secondly, some patients missed the holistic and direct care available in their home countries. Finally, patients were satisfied with the Norwegian health-care system because of its compassion, care, and respect toward them as well as advanced health-care equipment. Conclusion Arabic-speaking patients in Norwegian hospitals experienced long waiting times and linguistic problems. Hence, a better and specialized interpreter service may resolve problems emanating from communication within the system and the subsequent delays in treatment. Compassionate care and the feeling of respect and love is the core strength of the Norwegian system as perceived by the patients.